Histopathological changes induced in the gill of an. estuarine mullet, Liza parsia, by sublethal exposure to mercuric chloride - Pandey, A K; George, K C; Mohamed, M Peer (Indian Journal of Fisheries, 2011)
Sublethal exposure of Liza parsia to HgCl2 (0.5 ppm) elicited erratic swimming pattern, loss of equilibrium and respiratory distress during the initial 24 hrs. On day 2, copious secretion of mucus, swelling (hypertrophy) and vacuolization of the epithelial lining cells of secondary gill lamellae were noticed. Oedema and oedematous separation of epidermis from the basement membrane as well as necrosis and desquamation of epithelial cells were observed by day 4. Oedematous changes, particularly at the base of primary lamellae, tissue hyperplasia and fusion of secondary gill lamellae were seen on day 8 of the treatment. Extensive cellular hyperplasia, desquamation of epithelial cells, congestion of blood vessels and lamellar telangectases (aneurysms) were frequently encountered on day 10 and the entire interlamellar spaces became filled with the hyperplastic epithelium by day 15 of HgCl2 intoxication